UiTM Mukah English lecturers participate in the open summer programme 2024 / Stefanie Natasha Rich Joseph and Cindy Robert - Joseph, Stefanie Natasha Rich; Robert, Cindy (Corporate Communication Unit, UiTM Mukah Campus, 2024)
From July to August 2024, two English lecturers from UiTM Sarawak Branch, Mukah Campus, Miss Stefanie Natasha Rich Anak Joseph and Miss Cindy Anak Robert, took part in the prestigious OPEN (Online Professional English Network) Summer Programme. Over the span of nine weeks, they enrolled in the course "Using Educational Technology in the English Language Classroom", offered by Iowa State University, USA. Sponsored by the U.S. Department of State, funded by the U.S. Government, and administered by FHI 360, this programme aimed to elevate English language teaching and learning through innovative technology integration.